The influence of hydrogen loading and the fabrication process on the mechanical strength of optical fibre Bragg gratings. - Wei, C. Y.; Ye, Chen-Chun; James, Stephen W.; Tatam, Ralph P.; Irving, Phil E. (Elsevier Science B.V., Amsterdam., 2002)
This paper investigates the influence of hydrogen loading and other stages of the fabrication process on the mechanical strength of fibre Bragg gratings. Following UV irradiation, tensile tests were carried out on Ge–B codoped photosensitive fibres with and without hydrogen loading. Fibre Bragg gratings (FBGs) were written using a range of UV wavelengths, namely 246, 255 and 266 nm. The tensile strength of the optical fibres was determined in their as-received status and following the various stages of FBG fabrication. The mechanical strength was assessed using Weibull statistics. The results indicate that the strength of FBGs is influenced by the UV irradiation parameters and by the hydrogen-loading process. FBGs fabricated using shorter UV wavelengths and low pulse power intensity exhibit a high mechanical strength. The FBGs written in hydrogen loaded fibres have less than 50% of the strength of FBGs that have not been hydrogen loaded. Fibre fracture morphology observed by scanning electron microscope reveals fracture mechanisms of FBGs, which are correlated with the structural change of the silica fibres induced during the FBG inscription process. Combined with surface information gathered by atomic force microscopy, fracture mechanics is applied to understand the mechanisms of strength degradation caused by the FBG inscription proces
Keywords: Fibre Bragg grating strength; Hydrogen loaded optical fibre; Bragg grating formation mechanisms; Mechanical resistance of fibre Bragg gratings